1990
DOI: 10.1037/h0084242
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of structural ischemic brain damage to neurobehavioural deficit: The effect of postischemic MK-801.

Abstract: Global cerebral ischemia is well known to cause neuronal necrosis in selectively vulnerable sectors of the hippocampus. Since the hippocampus of the rat is involved in spatial navigation, learning, and memory, selective deficits in these abilities may arise from ischemic brain damage. Previous studies have shown (a) a detectable neurobehavioural deficit due to ischemic brain damage limited to half of the CA1 sector of the hippocampus and (b) a reduction of ischemic neuronal necrosis with the noncompetitive N-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 44 publications
(55 reference statements)
3
15
0
Order By: Relevance
“…Our findings agree with the Bachevalier and Meunier study who reviewed the relationship between hippocampal cell loss and cognitive deficits due to brain ischemia (28), also Rod, Kiyota and Milani (29)(30)(31). However findings of Green and Nunn did not show any correlation between these two parameters (1,32).…”
Section: Discussionsupporting
confidence: 64%
“…Our findings agree with the Bachevalier and Meunier study who reviewed the relationship between hippocampal cell loss and cognitive deficits due to brain ischemia (28), also Rod, Kiyota and Milani (29)(30)(31). However findings of Green and Nunn did not show any correlation between these two parameters (1,32).…”
Section: Discussionsupporting
confidence: 64%
“…The degree of histological protection was sufficient to be accompanied by improved performance on tasks of learning and memory carried out before histological analysis. 33 Based on the results discussed above, it is possible to reconcile apparently discrepant findings in the literature concerning the effect of MK-801 in global ischemia. It is clear that in temperature-controlled studies obviating hypothermia, MK-801 gives no significant protective effect in global ischemia.…”
Section: Discussionmentioning
confidence: 81%
“…The results showed that MK-801 did not reduce neuronal necrosis in the septal, densely ischemic CA1 pyramidal cells to a degree reaching statistical significance. 33 However, sections at coronal levels in the temporal hippocampus, incompletely ischemic due to continuing vertebrobasilar supply, did show significant protection. This was enough to significantly reduce overall necrosis at all levels of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurobehavioral performance in the water maze and also the radial arm maze appears to correlate with estimates of neuronal loss in the CA1 layer of the hippocampus. 42 Previously, we demonstrated a similar learning deficit after damage to structures other than the hippocampus, primarily the cortex. 29 It is not clear why extensive cortical damage interferes with visualspatial memory when the hippocampus is spared, although others have obtained similar results using different experimental models.…”
Section: Discussionmentioning
confidence: 99%